The Influence of Corporate Commitment on Employee Performance Through Industrial Relations Mediation at PT. INDOSPRING TBK - Iryanti, Desti; Rachmawaty, Mariana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
This study aims to examine the effect of corporate commitment on employee performance with industrial relations as a mediating variable at PT. Indospring Tbk. The background of this study is based on the decline in employee productivity influenced by high levels of absenteeism and involvement in negative behaviors, such as online gambling, as well as the importance of the role of industrial relations in maintaining work harmony. The method used is a quantitative explanatory approach with path analysis techniques and Sobel mediation tests on 130 permanent employee respondents. The results show that corporate commitment has a positive and significant effect on employee performance, both directly and through industrial relations mediation. The direct path coefficient value is 0.665, and the indirect effect through industrial relations is 0.409 with a Sobel Z value of 4.533 (p < 0.05). The conclusion of this study is that industrial relations strengthens the impact of corporate commitment on improving employee performance. The implications of this study emphasize the importance of commitment-based HR management strategies and industrial collaboration